2010
DOI: 10.1002/mnfr.200900085
|View full text |Cite
|
Sign up to set email alerts
|

PPARα L162V polymorphism alters the potential of n‐3 fatty acids to increase lipoprotein lipase activity

Abstract: Omega-3 fatty acids (FAs) may accelerate plasma triglyceride (TG) clearance by altering lipoprotein lipase (LPL) activity. Yet, the ability of n-3 FAs to increase LPL activity is dependent on transcription factors such as peroxisome proliferator-activated receptor alpha (PPARalpha). The objective was to examine the effects of n-3 FAs on LPL activity considering the occurrence of PPARalpha L162V polymorphism. First, 14 pairs of men either L162 homozygotes or carriers of the V162 allele were supplemented with n-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 43 publications
(39 reference statements)
1
17
0
1
Order By: Relevance
“…In addition, as they are involved in important transcriptional regulatory pathways, they increase PPAR-α, which regulates lipoprotein lipase (LPL) synthesis [38]. They also modulate genes involved in lipogenesis, together with nuclear receptors and transcription factors, including PPAR-γ, hepatocyte nuclear factor 4α (HNF-4α), LXR and nuclear factorkappa B (NF-κB) [46,37]. Therefore, they increase fatty acid oxidation by PPAR-α activation or by reducing SREBP activity, inhibiting lipogenesis [39,40].…”
Section: Unsaturated Fatty Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, as they are involved in important transcriptional regulatory pathways, they increase PPAR-α, which regulates lipoprotein lipase (LPL) synthesis [38]. They also modulate genes involved in lipogenesis, together with nuclear receptors and transcription factors, including PPAR-γ, hepatocyte nuclear factor 4α (HNF-4α), LXR and nuclear factorkappa B (NF-κB) [46,37]. Therefore, they increase fatty acid oxidation by PPAR-α activation or by reducing SREBP activity, inhibiting lipogenesis [39,40].…”
Section: Unsaturated Fatty Acidsmentioning
confidence: 99%
“…These unsaturated long-chain ω-3 fatty acids influence the physical properties of membranes (e.g., fluidity, thickness and deformability) and, consequently, interfere with transmembrane protein activity [34]. They are related to the moderate reduction of triacylglycerols by impairing diacylglycerol acyltransferase activity, which is critical in hepatic triacylglycerol synthesis [35], thus decreasing hepatic VLDL secretion [36], but high doses may adversely decrease LDL receptor and produce small LDL, which is related to atherosclerosis [37]. In addition, as they are involved in important transcriptional regulatory pathways, they increase PPAR-α, which regulates lipoprotein lipase (LPL) synthesis [38].…”
Section: Unsaturated Fatty Acidsmentioning
confidence: 99%
“…For example, in vitro studies demonstrated that the effects of omega-3 fatty acids supplementation on plasma triglyceride clearance through increasing transcription rates of lipoprotein lipase (LPL) gene, were dependent on the L162V polymorphism in the peroxisome proliferator-activated receptor alpha ( PPARA ) gene [102]. Another study reported that gene expression levels of PPARA and apolipoprotein A1 ( APOA1 ) were influenced by the PPARA L162V polymorphism after the supplementation of omega-3 fatty acids [103].…”
Section: Diet and Epigenetic Signaturesmentioning
confidence: 99%
“…In spite of its functional significance [18], the PPAR α Leu162Val was not associated with dietary fat intakes. These results are in accordance with those of Robitaille et al [19].…”
Section: Discussionmentioning
confidence: 99%
“…One missense mutation has been identified at codon 162 (Leu162Val) which results in the substitution of a leucine for a valine [17]. This mutation results in a lower transcriptional activity and a deteriorated metabolic profile for carriers of the Val162 allele [17,18,19]. PPAR γ is mostly expressed in adipose tissue and is involved in adipocyte differentiation [20].…”
Section: Introductionmentioning
confidence: 99%